2019
DOI: 10.1128/msystems.00261-18
|View full text |Cite
|
Sign up to set email alerts
|

Feed Restriction Modifies Intestinal Microbiota-Host Mucosal Networking in Chickens Divergent in Residual Feed Intake

Abstract: The impact of the FE-associated differences in feed intake on intestinal bacterial and host physiological parameters has so far not been clarified. Understanding the underlying principles is essential for the development of cost-effective strategies to improve FE in chicken production. Under conditions of quantitative feed restriction, low- and high-RFI chickens ate the same amount of feed. Therefore, this research helps in distinguishing intestinal bacterial taxa and functions that were highly reliant on feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 37 publications
(61 reference statements)
2
35
1
Order By: Relevance
“…A recent study has shown that dietary supplementation with STE could alter the microflora distribution in the cecum of broiler chickens ( Wu et al., 2019 ). The gut microbiota plays an important role in producing short-chain fatty acids and neuropeptides, which could affect the feed intake of animals ( Cryan et al., 2019 , Metzler-Zebeli et al., 2019a , Metzler-Zebeli et al., 2019b ). Because chickens are insensitive to sweet taste, promoted feed intake induced by STE supplementation might be associated with orexigenic neuropeptides secreted by the gut microbiota or the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that dietary supplementation with STE could alter the microflora distribution in the cecum of broiler chickens ( Wu et al., 2019 ). The gut microbiota plays an important role in producing short-chain fatty acids and neuropeptides, which could affect the feed intake of animals ( Cryan et al., 2019 , Metzler-Zebeli et al., 2019a , Metzler-Zebeli et al., 2019b ). Because chickens are insensitive to sweet taste, promoted feed intake induced by STE supplementation might be associated with orexigenic neuropeptides secreted by the gut microbiota or the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence data were analyzed with the Quantitative Insights Into Microbial Ecology (QIIME) package version 1.9.1 (Caporaso et al, 2010) as previously described (Metzler-Zebeli et al, 2019). The sequences for the eight FMT samples (Siegerstetter et al, 2018a) were re-analyzed together with the current dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Primers for target genes and housekeeping genes (HKG) as well as amplification conditions used were recently published by our group (Metzler-Zebeli et al, 2019). Amplifications were performed on the CFX96 Touch Real-Time PCR Detection System (Bio-Rad Laboratories Ges.m.b.H, Wien, Austria) using the following conditions: 95°C for 5 min, followed by 95°C for 10 s, 60°C for 30 s, and 72°C for 30 s for 40 cycles, followed by the generation of dissociation curves.…”
Section: Methodsmentioning
confidence: 99%
“…Lactobacillus species have been usually correlated with higher performance and better health [19]. In contrast, two studies have reported Lactobacillus species in the ileum to be associated with low productivity [20].…”
Section: Chicken Productivity and Its Relationship With The Gut Micromentioning
confidence: 99%
“…However, the relationship between the gut microbiota composition and productive performance of chickens has not yet been fully elucidated. Some authors have reported that high feed efficiency is associated with less diverse gut microbiota in chicken [20], while others have linked higher bacterial communities' complexity and richness with better feed efficiency [21].…”
Section: Chicken Productivity and Its Relationship With The Gut Micromentioning
confidence: 99%